A miniaturized millimeter-wave standing-wave filtering switch with high P1dB - Ma, Kaixue (2013)
This paper presents the design considerations of a silicon-based transmit/receive (T/R) switch for microwave and millimeter-wave frequencies. Techniques for minimizing switch size and loss while increasing linearity are discussed. With the dedicated idea of the standing-wave concept, a combo design of a bandpass filter and switch, called the filtering switch, is introduced for the front-end system to achieve better performance in terms of low insertion loss, compact size, and good linearity simultaneously. Based on the proposed switchable artificial resonator, a standing-wave single-pole single-throw (SPST) and a single-pole double-throw (SPDT) filtering switches are designed and implemented for demonstration. Fabricated with a 0.18- μm SiGe BiCMOS process, the standing-wave SPST exhibits only 1.9-dB insertion loss and 18-dB isolation with a compact chip area of only 0.027 mm2 at 50 GHz. The SPDT T/R switch exhibits 3.2-dB insertion loss, good stopband rejection, and 20-dB isolation with only 0.0675 mm2 active chip area at 60 GHz. With the proposed standing-wave topology, a good linearity with the input 1-dB compression point (P1dB) of 21 dBm is obtained for both switches.